Illegitimacy in oil palm (Elaeis guineensisJacq.) half-sib families and comparative molecular marker mapping associated with basal stem rot disease using single locus DNA microsatellite markers - Hama-Ali, Emad Omer (2013)
The oil palm Elaeis guineensisJacq., is a source of commercial planting material that makes oil palm an important oil crop in the world. Oil palm breeding has been progressing very well in Southeast Asia, especially in Malaysia and Indonesia. Despite the progress, there are still problems due to the difficulty of controlled crossing in oil palm. Contamination/illegitimate progeny has appeared in some breeding programs which causes a waste of money, time and labor once it is detected by the traditional method. Also, oil palm is badly affected by basal stem rot (BSR) disease in Southeast Asia. BSR disease is caused by the fungusGanoderma boninense, which is a major threat to oil palm compared with other Ganoderma sp. Breeders’ information suggested that there is no error in the assignment of parents to these breeding families (Family-1, Family-2, Family-3 and Family-4). As such, the use of molecular markers is necessary for breeding program management especially for perennial crops like oil palm and the use of molecular markers associated with BSR disease will accelerate the identification of resistant planting materials. The goals of these studies were to establish a procedure for sibship assignment,detection of illegitimacy and examination of a possible association between Ganoderma disease incidences (GDI) in an oil palm breeding program by using microsatellite markers. In the first study, four half-sib families (Family-1, Family-2,Family-3 and Family-4) were investigated, each with 50 offsprings with their candidate parents using 69 microsatellite loci. Among the 69 polymorphic microsatellite loci tested, 30 were selected based on high polymorphic information content (PIC) values and absence of null allele, for parental and sib-ship assignments. The parental palms stated by the breeder in the first study are not the true parents as revealed by the microsatellite loci gel patterns. The results of the parental assignments using the CERVUS program showed negative LOD score for all candidate parents FD6 (-37.5), FD8 (-31.1), FD10 (-34.6), FD 1/224 (-9.98),FP1/28 (-14.2) and FP1/10 (-9.63). These negative LOD scores revealed that these candidate parents were not the true parents for all progeny tested. The COLONY analysis results showed that 16 loci were sufficient for obtaining correct family assignments by using short run and pair likelihood-score (PLS) methods in the four half-sib families. The COLONY results gave two half-sib dyads. A probability of one in the first dyad resulted in three half-sib families namely,Family-1, Family-2, and Family-3, in which they shared the same father. The second dyad gave four half-sib families Family-1 (offspring ID 1 to 50), Family-2 (offspring 52 to 100, but not including offspring ID 74 and 97), Family-3 (offspring ID 101 to 150) and family-4 (offspring ID 151 to 200, not including offspring ID 180) with a probability of one as their fathers were sibs. In addition, correct pedigree reconstructions were done by COLONY from offspring genotypic data. The best configuration output gave four mothers for each family and one father for all the families. Furthermore, three (1.5%) illegitimate offsprings (offspring ID 51, 97 and 180) were detected among the 200 offsprings in this study by COLONY. The STRUCTURE software results presented four pure clusters (families), which is the same as the COLONY results and in 100% agreement with the breeders’documentation. In addition, all illegitimate offsprings (offsprings ID 51, ID 97, and ID 180) were detected among the progeny of the controlled crosses as admixed individuals in the clusters, and offspring ID 74 was assigned to the correct family. Moreover, from the STRUCTURE analyses, the sources of the illegitimate offsprings were detected. Illegitimate offspring ID 51 and ID 97 wereproduced during pollination (hybridization) time. Offspring ID 180 was caused by this seedling being mixed with those of other families in the nursery stage. In addition, possible associations between Ganoderma disease incidences (GDI) in three oil palm progeny types (KA4G1, KA4G8, and KA14G8) and 58 microsatellite markers were examined. The results of GDI showed that KA4G1 is a resistant progeny type against G. boninense, whereas KA4G8 and KA14G8 are susceptible progeny types. The icrosatellite markers produced 319 alleles in the three oil palm progeny types, and the average as 5.51 alleles per locus. Five markers,mEgCIR0793:180, mEgCIR0894:200, mEgCIR03295:210, mEgCIR3737:146, and mEgCIR3785:299, were found to be associated with Ganoderma disease with Pvaluesof 0.018, 0.033, 0.037, 0.034 and 0.037, respectively, in the single progeny analysis. In the pooled data (KA4G1, KA4G8, and KA14G8), 89 alleles from 46 loci were associated with GDI. Among the 89 significantalleles, 59 alleles showed significance at P <0.01and 30 alleles had significance at P <0.05.